The Role and Impact of Governance and Evaluation in Enhancing the Quality of Implementation of Construction Projects by Non-Profit Organizations in the Arabian Gulf region and their representatives between 2018 and 2022 - Abdel Sadek, Ezzat Hassane Ali; Magableh, Ghazi Mustafa (Journal of Economic, Administrative and Legal Sciences, 2024)
This research investigates non-governmental organizations (NGOs) and their construction projects. It explores the procedures and standards NGOs employ during project implementation and highlights the role of governance in ensuring successful project delivery. The study focuses on four key determinants of project success which are: scope, time, cost, and quality standards. Data was collected through a 105-item questionnaire distributed to 50 non-profit organizations within the Gulf region and their international representatives. The research methodology employed a descriptive and analytical approach, incorporating both inductive and quantitative methods, alongside qualitative analysis.  Statistical analysis of the questionnaire data was analyzed using SPSS software. The findings identify the strengths and weaknesses of NGOs in managing construction projects. They emphasize that adhering to governance principles during project implementation safeguards against setbacks and failures.  The results reveal a statistically significant relationship between an organization's commitment to governance and evaluation principles and the successful achievement of project objectives. Furthermore, a positive correlation exists between enhanced project execution quality and the evaluation process. This correlation allows for predicting project execution quality based on the number of evaluations conducted, as represented by the equation: Enhancement of construction project implementation quality = 1.398 + 0.512 x (Number of evaluations).
Keywords: NGOs; Governance of Organizations; Project Quality; Project Evaluation; Project Governance